Multivariate analysis of important squirrel cage motor parameters - Nutu, Catalin Silviu (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This paper regards the multivariate analysis of data for a three phase asynchronous electrical machine of 300 W equipped with a squirrel cage rotor. The recorded data are the following parameters of the motor: torque (M), rotation speed (n), voltage (U) and current (I). The aforementioned parameters are measured for both, the star and the delta configuration and this data measured is the basis of the multivariate analysis proposed by this paper.